A proposed methodology for analysing the translation of prose fiction texts with a narratively bound ironic component - Coromines i Calders, Diana (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Considering literary irony as an attitude rather than a figure of speech may have some methodological advantages for the analysis of its translation. It allows us to approach the narrative universe of certain prose fiction texts as ironically determined; to select only those translated ironic passages that are narratively relevant – and thus representative; and to reach conclusions on a possible macrostructural impact. The ultimate objective of this paper is twofold: Its first aim is to present a methodology for analysing the translation of any prose fiction text, in which irony plays an essential narrative role, taking as a prime example the German novel Im Krebsgang by Günter Grass and its translations into English, Danish, Catalan and Spanish. Its second aim is to propose a provisional taxonomy of strategies used to express irony in original texts (source texts) and in translated texts (target texts).